Design, Synthesis, and Biological Activities of Novel 2-Cyanoacrylate Compounds Containing Substituted Pyrazolyl or 1,2,3-Triazolyl Moiety - Yang Wang; Yudie Chen; Ye Qian; Jia Chen; Xianchao Du; Yujun Shi; Baolin Xu; Sheng Hua; Hong Dai (Molecules, 2023)
To develop novel 2-cyanoacrylate derivatives with potential bioactivity, a number of 2-cyanoacrylate compounds, including substituted pyrazole or 1,2,3-triazole ring, were designed, prepared, and structurally detected by 1H NMR, 13C NMR, and elemental analysis. The biological assessment displayed that some designed compounds had significant herbicidal activities against Brassica juncea, Chenopodium serotinum, Rumex acetosa, Alopecurus aequalis, Polypogon fugax, and Poa annua at a dosage of 1500 g/ha. Furthermore, some derivatives still expressed satisfactory herbicidal activities against Brassica juncea, Chenopodium serotinum, and Rumex acetosa when the dosage was lowered to 150 g/ha, especially the inhibitory effects of compounds 9a, 9d, 9f, 9i, 10a, 10b, 10e, and 10n against Brassica juncea were all over 80%, compounds 9d, 9f, 9g, 9h, 9i, 10h, 10i, 10m, 10n, and 10o possessed more than 70% inhibition rates against Chenopodium serotinum, and compound 9d indicated 70% herbicidal activity against Rumex acetosa. These results provided an important basis for further design and discovery of biologically active 2-cyanoacrylate compounds.